Managing Teacher Competence Development through the POLC Approach: Study of Senior High Schools in Ciamis - Irany Minorita Putri; Ahmad Rifandi (At Turots: Jurnal Pendidikan Islam, 2026)
This study examines the role of principal leadership based on the Planning, Organizing, Leading, and Controlling (POLC) management framework in enhancing teacher competence and promoting instructional innovation in senior high schools. Using a qualitative case study design, data were collected through in-depth interviews, participatory observations, and documentation from two research sites: SMAN 1 Ciamis and SMAN 1 Manonjaya. The participants included principals, teachers, and students selected through purposive sampling. Data analysis followed the Miles and Huberman model, involving data reduction, presentation, and conclusion drawing, while validity was ensured through triangulation and member checking. The findings reveal that both schools implement the POLC functions in a coherent and contextually adaptive manner. The planning process integrates institutional vision with teacher development goals through participatory and data-driven approaches. The organizing function ensures collaborative structures and distributed leadership that support innovation. The leading function highlights the principal’s transformational and participatory leadership in motivating and empowering teachers. Meanwhile, the controlling function emphasizes reflective supervision and continuous feedback as tools for professional improvement. The study concludes that the integration of the POLC management cycle with participatory and transformational leadership principles effectively strengthens a culture of innovation and continuous learning. This finding supports Schermerhorn (2017) on the adaptive nature of management, as well as Narti (2022) and Mamonto (2023) on the significance of participatory and transformational leadership in driving teacher creativity and institutional improvement. Practically, the research offers a conceptual framework for developing school leadership practices that align managerial discipline with humanistic engagement, enabling schools to function as adaptive, innovation-oriented learning organizations in the era of educational disruption.